Rare Earth Doped SnO(2) Nanoscaled Powders and Coatings: Enhanced Photoluminescence in Water and Waveguiding Properties - Goncalves, R. R.; Messaddeq, Younes [UNESP]; Aegerter, M. A.; Ribeiro, Sidney José Lima [UNESP] (Amer Scientific Publishers, 2011)
Luminescent Eu(3+) and Er(3+) doped SnO(2) powders have been prepared by Sn(4+) hydrolysis followed by a controlled growth reaction using a particle's surface modifier in order to avoid particles aggregation. The powders so obtained doped with up to 2 mol% rare earth ions are fully redispersable in water at pH > 8 and present the cassiterite structure. Particles size range from 3 to 10 nm as determined by Photon Correlation Spectroscopy. Rare earth ions were found to be essentially incorporated into the cassiterite structure, substituting for Sn(4+), for doping concentration smaller than 0.05 mol%. For higher concentration they are also located at the particles surface. The presence of Eu(3+) ions at the surface of the particles hinder their growth and has therefore allowed the preparation of new materials consisting of water redispersable powders coated with Eu(3+)-beta dike-tonate complexes. Enhanced UV excited photoluminescence was observed in water. SnO(2) single layers with thickness up to 200 nm and multilayer coatings were spin coated on borosilicate glass substrates from the colloidal suspensions. Waveguiding properties were evaluated by the prism coupling technique. For a 0.3 mu m planar waveguide single propagating mode was observed with attenuation coefficient of 3.5 dB/cm at 632.8 nm.
Keywords: Tin Oxide; Nanoparticles; Luminescence; Planar Waveguide; Erbium; Europium